Evaluasi Program Market Day di TK Triana Menggunakan Model CIPP - Anis Andina; Arina Rafa Dina; Astiyah Andini; Inestasia Br. Simanjuntak; Rahel Sentina Stefani Aritoang; Yolanda Agustina Sihombing (Jurnal Pena Pendidikan Dasar, 2026)
This study aims to evaluate the implementation of the Market Day program at Triana Kindergarten as part of early childhood learning. The study used a descriptive evaluative approach using the CIPP (Context, Input, Process, Product) model. Subjects included teachers, parents, and students. Data collection was conducted through observation, questionnaires, and documentation. The results indicate that, from a contextual perspective, the Market Day program aligns with children's developmental needs and learning objectives. From an input perspective, teacher readiness, parental involvement, and the availability of supporting facilities are in the very good category. From a process perspective, the implementation of activities is active, participatory, and aligned with the learning characteristics of early childhood. From a product perspective, the Market Day program has a positive impact on the development of children's communication skills, social interaction, cooperation, independence, responsibility, and early numeracy understanding in real-life situations. Furthermore, the level of satisfaction of teachers, parents, and students is in the very good category. Based on these results, it can be concluded that the Market Day program is effective and feasible for sustainable implementation, and is recommended as an alternative contextual learning program that supports the development of abilities and character in early childhood.